حیوانات کی حلت وحرمت: فقہا کی آراء اور علم حیوانات - حافظ مبشر حسین (FIKR-O NAZAR فکر ونظر, 2012)
The jurists of Islamic Law have laid down broad principles regarding the categorizing of the animals that are permissible or otherwise for consumption and utilization. These principles can be precisely stated as follows: 1-animals that have been identified in Quran or Sunnah in terms of their impermissibility; 2- animals not identified, yet fall under principles mentioned in Quran or Sunnah prohibiting their consumption or utilization. All other animals are initially permissible. While applying these principles in identifying the animals for each principle there exist various opinions among the jurists, this article seeks to reconsider these categorization with zoological division of the animal kingdom۔